A-X-L [videorecording (DVD)] - Daly, Oliver; Daly, Oliver; G, Becky, 1997-; Jane, Thomas; Neustaedter, Alex, 1998- (Sony Pictures Home Entertainment, 2018)
After an experiment gone wrong, a robotic dog developed by the military gets stranded in the desert and is found by a kind-hearted man who finds a way to connect with the dog and establish a special friendship with it based on mutual trust and loyalty.